Spectrum of paired‐like homeobox 2b immunoexpression in pediatric brain tumors with embryonal morphology. Issue 8 (28th June 2022) - Alturkustani, Murad; Walker, Adam D.; Tran, Ivy; Snuderl, Matija; Cotter, Jennifer A.
Abstract: Paired‐like homeobox 2b (PHOX2B) is an established immunomarker for peripheral neuroblastoma and autonomic nervous system cells. We aimed to evaluate the utility of PHOX2B immunostaining in central nervous system (CNS) tumors with embryonal morphology. Fifty‐one tumors were stained with PHOX2B and submitted for whole slide image analysis: 35 CNS tumors with embryonal morphology (31 CNS embryonal tumors and four gliomas); and 16 peripheral neuroblastomas were included for comparison. Diffuse nuclear immunopositivity was observed in all (16/16) neuroblastomas (primary and metastatic). Among CNS embryonal tumors, focal immunoreactivity for PHOX2B was observed in most (5/7) embryonal tumors with multilayered rosettes (ETMR) and a single high‐grade neuroepithelial tumor (HGNET) with PLAGL2 amplification; the remaining 27 CNS tumors were essentially immunonegative (<0.05% positive). Among ETMR, PHOX2B expression was observed in a small overall proportion (0.04%–4.94%) of neoplastic cells but focally reached up to 39% in 1 mm 'hot spot' areas. In the PLAGL2 ‐amplified case, 0.09% of the total neoplastic population was immunoreactive, with 0.53% in the 'hot spot' area. Care should be taken in interpreting PHOX2B immunopositivity in a differential diagnosis that includes metastatic neuroblastoma and CNS tumors; focal or patchy expression should not be considered definitively diagnostic of metastatic peripheral neuroblastoma.